Faktor Risiko Gangguan Pendengaran pada Pekerja Industri - Afriza Alfwandy Winata (Jurnal Medika Hutama, 2022)
Industry is a sector that uses humans as workers. This creates several problems for workers, one of which is the hearing system. Hearing loss in workers is one of the diseases that can be caused by factors in the work environment or outside. These factors are identified to determine the prevention or control of hearing loss. The purpose of this study was to determine the risk factors for hearing loss in industrial workers. The literature study uses literature review articles and research articles in international and national journals in the last 10 years. Results: From several studies that have been carried out, the authors conclude that the risk factors for hearing loss in industrial workers are noise intensity, use of PPE, years of service, and age.